Modelowanie wpływu transformacji systemowej na funkcjonowanie rynków - wybrane metody - Jakubowski, Rafał M. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the postsocialistic countries at the beginning of the 90's, markets were characterized of the high level of the dead-weight welfare lost. The economic transition triggered off some market processes which supposedly should rise to increasing of market efficiency. The main objective of the investigation - presented in this article - was choosing the theoretical tools for microeconomical analysis of these processes which is necessary to the proper institutionalization and regulation of markets. In the first part, some basic ideas and definitions are explained. In the next parts, the theoretical (classical and hedonic) models and the experimental methods were refined. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 137-148